2009
DOI: 10.1016/j.jastp.2009.08.007
|View full text |Cite
|
Sign up to set email alerts
|

First incoherent scatter radar observations of ionospheric heating on the second electron gyro-harmonic

Abstract: a b s t r a c tWe report first results from a unique experiment performed at the HIPAS ionospheric modification facility in conjunction with the Poker Flat incoherent scatter radar in Alaska. High-power radio waves at 2.85 MHz, which corresponds to the second electron gyro-harmonic at $ 245 km altitude, were transmitted into the nighttime ionosphere. Clear evidence of F-region ionospheric electron temperature enhancements were found, for the first time at this pump frequency, maximizing when the pump frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Figure compares representative ion‐line power spectra associated with natural turbulence (Figure a) and heater‐induced turbulence (Figure b), both observed with PFISR. The heater‐induced turbulence was generated by the High Power Auroral Stimulation heater, which was located ~35 km from PFISR [ Kosch et al ., ]. In each case, the spectra were calculated using a 72 km long pulse.…”
Section: Observationsmentioning
confidence: 99%
“…Figure compares representative ion‐line power spectra associated with natural turbulence (Figure a) and heater‐induced turbulence (Figure b), both observed with PFISR. The heater‐induced turbulence was generated by the High Power Auroral Stimulation heater, which was located ~35 km from PFISR [ Kosch et al ., ]. In each case, the spectra were calculated using a 72 km long pulse.…”
Section: Observationsmentioning
confidence: 99%
“…This suggests that at high latitudes, the excitation of UH waves and FAI are the major source of electron heating, though other mechanisms are not excluded. The behavior around the second gyroharmonic is an exception: Kosch et al [2009] found that electron heating maximized around the second gyroharmonic.…”
Section: Introductionmentioning
confidence: 99%
“…Electron acceleration and heating is a fundamental process in space physics. It is observed in the F-region ionosphere (Lund et al, 2012;Schunk & Nagy, 1978), in auroral cavity regions (Menietti et al, 1994;Morgan et al, 2000), in active ionosphere modification experiments (Kosch et al, 2009;Robinson et al, 1996), in solar wind turbulence (Sahraoui et al, 2009), in magnetosphere reconnection (Phan et al, 2013), and in the bow shock (Chen et al, 2018). Many radar and satellite measurements show that ionospheric thermal electrons (of the order 0.1 eV) are often heated up to several eV near the F-region ionosphere (Curtis et al, 1985;Lund et al, 2012;Schunk & Nagy, 1978;Seo et al, 1997).…”
Section: Introductionmentioning
confidence: 99%